ASSOCIATION OF PROSTATE DISORDERS WITH RENAL DYSFUNCTION: ROLE OF BIOCHEMICAL MARKERS - RESHMA K; Dr.SUDHA K; MAMATHA S (International Journal of Pharma and Bio Sciences, 2014)
Prostate disorders like prostatitis,Benign prostatic hyperplasia (BPH) and prostatitis are the most common disorders of the male population, the latter two being prevalent in the elderly men.PSA being the gold standard parameter to identify these diseases, is not of much importance in the differential diagnosis of prostate disorders. This study focuses on the of blood levels of PSA, Urea, BUN, Creatinine BUN/creatinine ratio and eGFR and the correlations between these parameters and note the association of various disorders of prostate with renal dysfunction. Serum sample obtained from 25 patients each ,diagnosed to have prostatitis,BPH and carcinoma prostate were analysed for the parameters mentioned above. Results indicated that there was a significant negative correlation of eGFR with PSA and a significant positive correlation of eGFR with BUN/creatinine ratio in patients diagnosed with BPH. No other parameters correlated in other disorders were found to be significant. Based on our results we conclude that patients with BPH are most likely to progress into kidney dysfunction and also that eGFR may be a better marker as compared to BUN/creatinine ratio in the assessment of kidney damage consequent to prostate hypertrophy.